2012
DOI: 10.1097/ogx.0b013e3182547170
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of Bevacizumab in the Primary Treatment of Ovarian Cancer

Abstract: BACKGROUNDVascular endothelial growth factor is a key promoter of angiogenesis and disease progression in epithelial ovarian cancer. Bevacizumab, a humanized anti-vascular endothelial growth factor monoclonal antibody, has shown single-agent activity in women with recurrent tumors. Thus, we aimed to evaluate the addition of bevacizumab to standard front-line therapy. RESULTSOverall, 1873 women were enrolled. The median progression-free survival was 10.3 months in the control group, 11.2 in the bevacizumab-init… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
268
2
8

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 223 publications
(284 citation statements)
references
References 14 publications
6
268
2
8
Order By: Relevance
“…Bevacizumab 7.5-15 mg/kg every 3 weeks may be added to these regimens [67,68]. Two studies have reported a modest, but statistically significant increase in progression-free survival in patients receiving maintenance bevacizumab following carboplatin, paclitaxel, and concurrent bevacizumab [67,68].…”
Section: Chemotherapy For Advanced Stage Ovarian Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Bevacizumab 7.5-15 mg/kg every 3 weeks may be added to these regimens [67,68]. Two studies have reported a modest, but statistically significant increase in progression-free survival in patients receiving maintenance bevacizumab following carboplatin, paclitaxel, and concurrent bevacizumab [67,68].…”
Section: Chemotherapy For Advanced Stage Ovarian Cancermentioning
confidence: 99%
“…Two studies have reported a modest, but statistically significant increase in progression-free survival in patients receiving maintenance bevacizumab following carboplatin, paclitaxel, and concurrent bevacizumab [67,68]. There is no evidence as yet to demonstrate an overall survival benefit, but a subgroup analysis of the International Collaboration on Ovarian Neoplasms 7 (ICON7) trial found that there was an improved median survival (30.3 vs 39.4 months) in patients with suboptimal Stage III and Stage IV [67].…”
Section: Chemotherapy For Advanced Stage Ovarian Cancermentioning
confidence: 99%
“…(Table 1), bevacizumab (Avastin) was the first anti-angiogenesis agent to be advanced into the phase 3 randomized trial design for advanced EOC. To date, four pivotal trials have been completed, two in the primary setting and two for patients with recurrent disease (Table 2) [57][58][59][60][61][62][63][64][65][66].…”
Section: Phase 2 Studiesmentioning
confidence: 99%
“…Gynecologic Oncology Group (GOG) protocol 218 was a three-arm placebo-controlled study, with all patients receiving carboplatin and paclitaxel [58]. In the first experimental arm, patients were treated with concurrent bevacizumab (15 mg/kg) followed by placebo maintenance (bevacizumab-initiation), while in the second experimental arm, patients received concurrent and maintenance bevacizumab every 21 days for up to 16 doses (bevacizumab-throughout).…”
Section: Phase 2 Studiesmentioning
confidence: 99%
“…Although the molecular etiology about OC was continuously investigated (Samuels et al, 2011;Munksgaard et al, 2012), the overall survival rate of OC was still not improved in the last 20 to 30 years (Vaughan et al, 2011). In Robert's study, the poor prognosis of OC was usually attributed to advanced stage at diagnosis and inadequate chemotherapy (Burger et al, 2011), but it was difficult to solve these technical problems. Therefore, the prevention of OC seems to be particularly important.…”
Section: Introductionmentioning
confidence: 99%